Long-Term Safety and Usefulness of Mexiletine in a Large Cohort of Patients Affected by Non-dystrophic Myotonias - Modoni, Anna; D'Amico, Adele; Primiano, Guido; Capozzoli, Fiorentino; Desaphy, Jean-François; Lo Monaco, Mauro (Frontiers in Neurology, 2020)
Objective: The aim of our study was to evaluate long-term efficacy and safety of mexiletine in 112 patients affected by genetically confirmed non-dystrophic myotonias. The study was performed at the Neurophysiologic Division of Fondazione Policlinico Universitario A. Gemelli IRCCS, Rome and the Children’s Hospital Bambino Gesù, Rome. Methods: The treatment was accepted by 59 patients, according to clinical severity, individual needs, and concerns about a chronic medication. Forty-three patients were affected by recessive congenita myotonia, 11 by sodium channel myotonia, and 5 by dominant congenital myotonia. They underwent clinical examination, before and after starting therapy, and EMG. A number of recessive myotonia patients underwent a protocol of repetitive nerve stimulations, for detecting and quantifying the transitory weakness, and a modified version of the Timed Up and Go test, to document and quantify the gait impairment. Results: Treatment duration ranged from 1 month to 20 years and the daily dosages in adults ranged between 200 and 600 mg. No patient developed cardiac arrhythmias causing drug discontinuation. Mexiletine was suspended in 13 cases (22%); in 3 patients, affected by Sodium Channel myotonia, because flecainide showed better efficacy; in 1 patient because of a gastric cancer antecedent the treatment; in 4 patients because of untreatable dyspepsia; 5 patients considered the treatment not necessary. Conclusions: In our experience, mexiletine is very useful and not expensive. We did not observe any hazarding cardiac arrhythmias. Dyspepsia was the most frequent dose-limiting side effect.